2012
DOI: 10.1007/s10965-012-9906-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation and dynamic mechanical properties of PP/clay nanocomposites

Abstract: Polypropylene/clay nanocomposites were prepared by melt blending technique. A PP homopolymer was melt blended with commercial nanoclay masterbatch at different concentration (5, 10 and 15 wt% of nanoclay) using Laboratory Mixing Extruder (LME). The morphology of the nanocomposites was characterized using Scanning Electron Microscope (SEM). The viscoelastic and thermomechanical properties were analyzed via Dynamic Mechanical Analysis (DMA). The morphological analysis showed that the nanoclay was well distribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…So, even though the scratch depth in the ploughing mode for Cu(CHDA) is more than 1300 nm (elastic deformation), the residual prole is only 400 nm deep (plastic deformation). The elastic recovery of Cu(CHDA) is comparable with that of organic polymers and nanocomposites (60-80%), 44,45 while Cu(INA) 2 has a similar value as a scratched zeolite MFI lm (37%). 46 In order to further analyse the possible loss of mechanical integrity of the MOF lms, scratches were evaluated by SEM.…”
Section: Scratch Experimentsmentioning
confidence: 72%
“…So, even though the scratch depth in the ploughing mode for Cu(CHDA) is more than 1300 nm (elastic deformation), the residual prole is only 400 nm deep (plastic deformation). The elastic recovery of Cu(CHDA) is comparable with that of organic polymers and nanocomposites (60-80%), 44,45 while Cu(INA) 2 has a similar value as a scratched zeolite MFI lm (37%). 46 In order to further analyse the possible loss of mechanical integrity of the MOF lms, scratches were evaluated by SEM.…”
Section: Scratch Experimentsmentioning
confidence: 72%
“…Our interest lies in melt blending technique as it is simple, fast and economical method compatible with current industrial techniques [14,40,41]. The idea of using melt blending technique in combination with nanoclay and compatibilizer is to achieve good dispersion of the nanofillers through shear forces as well as strong coupling/interface interaction between nanofiller and matrix [2,14,40].…”
Section: Introductionmentioning
confidence: 99%
“…where m5E f =E m (19) where E f is the Young's modulus of the filler. Counto assumed that perfect bonding occurs at matrixfiller interface and yielded the following equation [55].…”
Section: Tensile Parameters Modelingmentioning
confidence: 99%
“…It was reported that the cavitation predominant mechanism in the nanocomposites is nano-sized calcium carbonate (NCC)/ HDPE debonding [18]. Chafidz et al observed that CaCO 3 nanoparticles increase the crystallization temperature and crystallization rate of HDPE and reduce the yield stress [19]. Huang et al found addition of nanoscale calcium carbonate to HDPE leads to reduction of spherulite size [20].…”
Section: Introductionmentioning
confidence: 99%